Prevalence and risk factors analysis of bovine tuberculosis in cattle raised in mixed crop‐livestock farming system in Tigray region, Ethiopia. Issue 1 (19th November 2018) - Habitu, Takele; Areda, Demelash; Muwonge, Adrian; Tessema, Girum T.; Skjerve, Eystein; Gebrehiwot, Tadesse
Abstract: Bovine tuberculosis (BTB) is a disease of animal and public health importance in developing countries. In rural Ethiopia, there is potential for a shift in the epidemiologic of this disease driven by transformation of dairy industry. This includes gradual change from the traditional mixed crop‐livestock husbandry practice to a semi‐intensification system. It is therefore, essential to document the prevalence and risk factors of BTB to continuously update the designing and implementation of control and prevention strategies. Here, we present findings of a cross‐sectional study on the prevalence and associated risk factors of BTB among cattle reared under mixed crop‐livestock farming system in Tigray region, Ethiopia. A multistage purposive sampling approach was used to select districts, villages, herds and individual cattle. A total of 1, 357 cattle from 310 herds were examined for BTB infection using a comparative intradermal tuberculin skin test (CIDT). Questionnaires were used to gather data on herd structure and herd management practices. A multilevel logistic mixed effect model was used to determine risk factors after accounting for clustering effect at three levels (village, herd and individual animal). Overall prevalence of BTB was 4.3% (95% CI = 3.4–5.6), with the highest prevalence recorded in Alamata district (5.6%) and lowest in Korem (1.6%). Multilevel logistic mixed effect model analysis identified exotic breed (OR = 3, p = 0.014), closed barn (OR = 2.6, p = 0.018), large herd size (OR = 2.6, p = 0.05) and purchase of cattle (OR = 2.1, p = 0.027) as important risk factors for BTB. Taken together, these findings suggest that the current dairy development program centred on the introduction of exotic and or crossed animals could have contributed to changing epidemiological situations of BTB in the study area.